Influence of Duranta erecta Fruits Extract Prepared via Supercritical Fluid Extraction on Microbial Growth, Ultrastructure, in-vitro Wound Healing and Oxidant Stress - Mohammed Ibrahim Alghonaim (BioResources)
Diverse metabolites of plants exhibit various biological activities. Supercritical fluid extraction (SFE) was applied at various temperatures (40, 60, and 80 ºC) to extract Duranta erecta fruits. Maximum yield of extract (0.456 g) was obtained at 60 ºC; besides, at this temperature the release of gallic acid, chlorogenic acid, methyl gallate, rutin, naringenin, rosmarinic acid, daidzein, quercetin, and kaempferol were promoted in high concentrations of 3510, 277, 326, 571, 7460, 1060, 31000, 7770, and 103 µg/mL, respectively. Moreover, S. aureus, S. typhi, B. subtilis, E. coli, and C. albicans, were inhibited with highest inhibition zones such as 28±0.1, 27±0.2, 30±0.1, 25±0.1, and 30±0.2 mm, respectively at 60 ºC than that at other temperatures of the SFE. Low quantities of minimum inhibitory and minimum bactericidal concentrations of the extract were recorded at 60 ºC. Ultrastructural changes were observed in the exposed B. subtilis to D. erecta fruits extract at 60 and 80 ºC including irregular, and rupture of cell wall. Antioxidant potential of D. erecta fruits extract via DPPH was recorded with promising IC50 value of 9.66 µg/mL. Moreover, FRAP antioxidant activity was confirmed with 355 equivalent (AAE) µg/mg at 60 ºC. The fruits extract from D. erecta at 60 ºC of SFE conditions reflected excellent wound healing property.